PERENCANAAN PENGENDALIAN KECACATAN KERNEL DENGAN METODE STATISTICAL QUALITY CONTROL (SQC) DI PT. FAJAR BAIZURY AND BROTHER - Fitriadi Fitriadi; Muzakir Muzakir; Nova Ferika (Universitas Teuku Umar, 2018)
PT. Fajar Baizury and Brothers engaged in processing oil palm products. The palm oil plantation industry produces 2 types of products, namely palm oil and palm kernel core. This research is more focused on the palm kernel produced, especially in terms of the quality produced. The quality of the resulting kernel is of course good and some are defective. Defective kernel production results can cause problems for the company, because it can be detrimental. So the levels of defects needs to be reduced and controlled so as not to cause harm to the company. Defective kernel produced have three categories, there are moisture, dirt, and broken. The Seven Quality control device are used to reduce the type of disability produced. By using data that has been obtained during field observations and data from bookkeeping results provided by the company, then data processing can be done. The data used in this study is the production data from 2018. So as to reduce the type of defect that the kernel produced.